2010
DOI: 10.1364/oe.18.019966
|View full text |Cite
|
Sign up to set email alerts
|

Growth behavior of laser-induced damage on fused silica optics under UV, ns laser irradiation

Abstract: The growth behavior of laser-induced damage sites is affected by a large number of laser parameters as well as site morphology. Here we investigate the effects of pulse duration on the growth rate of damage sites located on the exit surface of fused silica optics. Results demonstrate a significant dependence of the growth parameters on laser pulse duration at 351 nm from 1 ns to 15 ns, including the observation of a dominant exponential versus linear, multiple-shot growth behavior for long and short pulses, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(47 citation statements)
references
References 21 publications
2
44
0
1
Order By: Relevance
“…Bold squares are very close to this line, meaning that the growth behavior can be described in average by a unique value at a given fluence. A growth threshold around 5 J/cm 2 is deduced from this experiment; it corresponds to the threshold previously reported by several authors [4][5][6][7][8][9][10][11][12][13][14][15][16]. Shot after shot, damage sites are bigger and bigger, but for a given laser energy deposition, the stresses developed by the pressure pulse remain equal for longer circumferential and radial cracks that are more numerous too.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Bold squares are very close to this line, meaning that the growth behavior can be described in average by a unique value at a given fluence. A growth threshold around 5 J/cm 2 is deduced from this experiment; it corresponds to the threshold previously reported by several authors [4][5][6][7][8][9][10][11][12][13][14][15][16]. Shot after shot, damage sites are bigger and bigger, but for a given laser energy deposition, the stresses developed by the pressure pulse remain equal for longer circumferential and radial cracks that are more numerous too.…”
Section: Resultssupporting
confidence: 86%
“…In this figure, a change in the slope in this semilogarithmic representation is perceptible too (dashed areas are just a guide for eye), meaning that other parameters are involved in the description of the growth. It is commonly admitted that the rear growth phenomenon is well characterized by an exponential behavior [4][5][6][7] except for shorter pulse duration where a linear growth is sometimes observed [6]. On this basis, we consider the singleshot growth rate coefficient k defined in Eq.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference possibly results from the site morphologies tested and the local fluence. Numerous researchers [9,13,18,19] have demonstrated that the complex damage growth process is affected not only by the various laser parameters but also the intrinsic structural features of the optical components. In general, there are various precursors on the optical surface that induce damage sites with different morphologies.…”
Section: Damage Growth Coefficientsmentioning
confidence: 99%